Mechanistic Features in Al(I)-Mediated Oxidative Addition of Aryl C–F Bonds: Insights From Density Functional Theory Calculations - Zhang, Xiangfei; Li, Ping; Wang, Binju; Cao, Zexing (Frontiers in Chemistry, 2019)
The oxidative addition of a range of robust aryl C−F bonds to a single Al(I) center supported by a (NacNac)− bidentate ligand ((NacNac)− = [ArNC(Me)CHC(Me)NAr]− and Ar = 2,6−Pri2C6H3) have been explored by density functional theory calculations. Our calculations demonstrate that the Al(I) center-mediated C−F insertion generally proceeds via the concerted mechanism that involve both the donation ( ) and back−donation ( ) interactions. In addition, the predicted free energy barriers for the C−F bond activation show good agreement with the experimental information available. Finally, the comparative studies show that B(I) is the most active among group III metals (B, Al, Ga), thus supplying a testable prediction for experiments.